BERBAGI PENGETAHUAN DAN KOMUNITAS ONLINE: SEBUAH FENOMENA BLOG - Winarno, Wahyu Agus (Faculty of Economics and Business, University of Muhammadiyah Malang, 2011)
The organizational problem is to create the effective collaboration processes in a organization. Weblog which constitutes a social software to facilitate knowledge sharing effectively. Meanwhile, blog in the intranet design, The objective to make communication easier to all employee or staff . The objective is to share knowledge or experience in order to solve the problem in a blog. Nevertheless, The member of online community will not face a constraint with hierarchy’s organization limitation.The other benefit is management can directly give feedback on staff comment in blog.